GENETIC DIVERSITY OF SAO MANG SPECIE (HOPEA RETICULATE TARDICU) BASED ON THE ANALYSES OF CHLOROPLAST DNA SEQUENCES AND RAPD MARKERS - Thành, Nguyễn Đức (Vietnam Journal of Biotechnology, 2011)
The application of molecular markers for assessment of genetic diversity of plant species has an important impact in development of new varieties and conservation of gene sources. In this study, the level of genetic diversity of 30 samples of Sao mang specie collected from Coi Leaf Foiling Forest, Ca Na mountain, Phan Rang province was evaluated using chloroplast DNA and RAPD markers. The results of the analyses of 16S chloroplast and trnL genes and spacers between trriD-tml, psbC-trnS, atpB-rbcLn genes showed that there were variations in, only, trnD- trnT region. Seven (OPB6, 0PB8, OPB20, 0PC6, OPC9, OPC12, and OPC 17) from 17 investigated RAPD primers gave low polymorphism in 30 investigated samples. With 7 polymorphic primers, 1463 DNA fragments were amplified, among them, 59 were polymorphic (4.03%). A dendrogram based on RAPD analyzed data and generated by UPGMA clustering analyses using Jaccard’s coefficient divided 30 samples of Sao mang into three main groups. The first group comprises 4 samples (S1.6, S1.9, S3.4 and S4.2), the second group includes 10 samples (Sll, S12, S13, S21, S22, S23, S24, S25, S26 and S41), and the third group consistes of 16 remained samples. Two samples (S53 va S55) had a highest genetic similarity, the value of that was 91%. The data obtained in this study showed that the level of genetic diversity of investigated Sao mang species is low, indicating the high degeneration of this species. Therefore, an effective strategy for conservation and development ofthe species are, exfremely, needed.